The Influence of Financial Influencers on Social Media on the Financial Behavior of Young Consumers in Gorontalo City - Desi Putri Dama; Baharuddin Semmaila; Baso Amang; Aryati Arafah; Muhammad Arif; Tenriawaru Tenriawaru (The Es Accounting And Finance, 2026)
This study aims to analyze the influence of influencer expertise, trustworthiness, and content attractiveness on the financial behavior of young consumers in Gorontalo City. The rapid growth of social media has positioned influencers as important sources of information that may shape financial decisions and behaviors among young people. However, previous studies have produced inconsistent findings regarding the influence of influencer characteristics on financial behavior. This study employed a quantitative approach using a survey method. The population consisted of young consumers in Gorontalo City who actively use social media and follow influencers. A total of 100 respondents were selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that influencer expertise has a positive and significant effect on young consumers' financial behavior, suggesting that influencers' knowledge and competence encourage better financial planning and management practices. Trustworthiness also has a positive and significant effect on financial behavior, indicating that credibility and integrity are important considerations in accepting financial information. Meanwhile, content attractiveness does not significantly affect financial behavior, implying that visual appeal and creative presentation are not the primary determinants of financial behavior among young consumers. Simultaneously, influencer expertise, trustworthiness, and content attractiveness significantly influence the financial behavior of young consumers in Gorontalo City.